2006
DOI: 10.1177/1358863x06073449
|View full text |Cite
|
Sign up to set email alerts
|

Renal artery calcium: relationship to systemic calcified atherosclerosis

Abstract: Abstract:In this study we tested the hypothesis that calcium due to atherosclerosis in the renal arteries would be significantly associated with calcium in multiple other vascular beds, independent of traditional risk factors for cardiovascular disease (CVD). Electron beam computed tomography was conducted in 1461 consecutive asymptomatic patients free of clinical CVD to determine the presence and extent of calcium in the renal arteries, coronary and non-coronary vasculature and the aortic and mitral annuli. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 33 publications
3
22
1
Order By: Relevance
“…studies of asymptomatic subjects by Allison et al found that calcification of all arterial beds was a significant predictor of MAC with the exception of the coronary, iliac and renal arteries, while the presence of abdominal aorta calcification gave the highest odds for MAC 110,111 . Nevertheless, other studies have found a strong association between the presence and extent of MAC and presence and progression of CAC 112,113 , although the prevalence of CAC appears to be much higher than prevalence of MAC (50% vs 9%) 114 .…”
Section: Mitral Valvementioning
confidence: 96%
See 2 more Smart Citations
“…studies of asymptomatic subjects by Allison et al found that calcification of all arterial beds was a significant predictor of MAC with the exception of the coronary, iliac and renal arteries, while the presence of abdominal aorta calcification gave the highest odds for MAC 110,111 . Nevertheless, other studies have found a strong association between the presence and extent of MAC and presence and progression of CAC 112,113 , although the prevalence of CAC appears to be much higher than prevalence of MAC (50% vs 9%) 114 .…”
Section: Mitral Valvementioning
confidence: 96%
“…In asymptomatic subjects, the presence of calcium in the abdominal aorta had the highest sensitivity for any renal artery calcification (94.5%) 49 . Risk factors were rarely assessed and generally it is only age and male gender, possibly with hypertension, that are consistently associated 50,51,52 , although, curiously, low body mass index and low diastolic blood pressure were risk factors for presence and extent respectively of subclavian artery calcification 53 .…”
Section: Other Arteriesmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the study of Aggarwal et al [1], atherosclerotic plaques were found in 75% of renal arteries in the fourth decade, in 85% in the fifth decade, in 70% in the sixth decade and in 100% in the seventh decade. Renal artery calcium was also significantly associated with age [3]. In the literature, some of the studies claimed that the plaques were not correlated with age [13].…”
Section: Atherosclerotic Plaques With Respect To Age Groupsmentioning
confidence: 97%
“…It has previously been reported that patients with MAC have a higher prevalence of coronary artery disease, arrhythmias, aortic valve calcification, and cerebrovascular diseases [2][3][4]. MAC and atherosclerosis have similar risk factors including old age, hypertension, diabetes, and obesity; it is hypothesized that the presence of MAC reflects the duration and intensity of exposure to these risk factors [5]. Myocardial repolarization abnormalities are correlated with ventricular arrhythmias and high cardiovascular mortality.…”
Section: Introductionmentioning
confidence: 99%